Apolipoprotein E genotype impact on memory and attention in older persons: the moderating role of personality phenotype. (14th June 2017) - Chapman, Benjamin P.; Benedict, Ralph H.B.; Lin, Feng; Roy, Shumita; Porteinsson, Antoine; Szigeti, Kinga; Federoff, Howard; Mapstone, Mark
Abstract : Objectives: To determine if phenotypic personality traits modify the association of Apolipoprotein E (APOE) genotypes with different domains of cognitive function. Design: Cross‐sectional. Methods: 172 non‐demented older adults were administered the NEO‐Five Factor Inventory (NEO‐FFI), a battery of neuropsychological tests assessing memory, attention, executive function, language, and visuospatial ability, and underwent APOE genotyping. Multivariate (multiple‐dependent variable) regression models predicting cognitive domains tested APOE interactions with personality traits, adjusting for age, sex, and education. Results: The APOE ε4 allele showed small to modest main effects on memory and executive function (1/3 SD deficits for carriers, p < .05), with ε2 status evidencing minimal and non‐significant benefit. Neuroticism interacted with both ε2 and ε4 alleles in associations with attention scores (p = .001), with ε2 benefits and ε4 deficits being marked at high Neuroticism (Mean [M] covariate‐adjusted Z‐score = .39 for ε2, −.47 for ε4). The association of ε4 with memory was moderated by Conscientiousness (p < .001), such that ε4 memory deficits were apparent at low Conscientiousness (M = −.56), but absent at high levels of Conscientiousness. Weaker patterns (p < .05) also suggested ε4‐related detriments in executive function only at lower Conscientiousness, and ε2 memory benefits only at higher Openness. Conclusions: Conscientiousness and Neuroticism moderate APOE associations with memory and executive function. As such, they may be useful phenotypic markers in refining the prognostic significance of this polymorphism. Effect‐modifying personality traits also provide clues about behavioral and psychological factors that influence the cognitive impact of APOE. Copyright © 2017 John Wiley & Sons, Ltd.